2010
DOI: 10.1007/s00468-010-0449-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding structural roots system of 5-year-old African plum tree (D. edulis) of seed and vegetative origins (G. Don) H. J. Lam

Abstract: Root morphology of 5-year-old trees of Dacryodes edulis (G. Don) H. J. Lam of seed and two vegetative (cutting and marcot) origins were assessed in Cameroon. Roots of D. edulis trees of seed and vegetative origins were totally excavated and their root morphology described and quantified. Trees of seed origin were characterized by a tap root, reaching depths of about 1.2 m. Contrarily trees of cutting origin showed three strong vertical roots (d [ 5 mm) with the longest reaching depths of 1.31 m. Trees of marco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…The results of our investigations on D. edulis indicate that trees of seed origin were characterized by a tap root, reaching depths of about 1.20 m, whereas trees of cutting origin showed three strong vertical roots (d > 5 mm) with the longest reaching depths of 1.31 m Similarly, trees of marcot origin were observed to have thick, relatively short prominent vertical roots, reaching depths of 1.15 m (Asaah et al, 2010) (Fig. 3).…”
Section: Summary Of Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The results of our investigations on D. edulis indicate that trees of seed origin were characterized by a tap root, reaching depths of about 1.20 m, whereas trees of cutting origin showed three strong vertical roots (d > 5 mm) with the longest reaching depths of 1.31 m Similarly, trees of marcot origin were observed to have thick, relatively short prominent vertical roots, reaching depths of 1.15 m (Asaah et al, 2010) (Fig. 3).…”
Section: Summary Of Resultsmentioning
confidence: 66%
“…The decrease in fine root volume of shea tree or karité (Vitellaria paradoxa) and néré (Parkia biglobosa) trees in the 0-20 cm soil stratum following root pruning during the cropping season has been reported to reduce tree x crop competition for below ground resources resulting in yield increase of (mostly annual) companion crops (Bayala et al, 2004). Several authors have examined the distribution of structural primary roots (Akinnifesi et al, 1999;Asaah et al, 2010;Coutts 1983;Toky and Khosla, 1989). Other research efforts have described and compared the fine root distribution of 8 tree species in India (Chaturvedi and Das, 2003); 13 multipurpose trees in Nigeria (Akinnifesi et al, 1999); Grevillea robusta and Gliricidia sepium in Kenya (Odhiambo et al, 2001); and Senna siamea in three regions of Togo (Vanlauwe et al, 2002).…”
Section: Rationalementioning
confidence: 99%
“…It is worth noticing that even if young cuttings of B. glabrifolia did not need IBA to develop roots, the number of roots increased signifi cantly when the hormone was applied to cuttings of both ages. A good root system is important for tree stability and growth (Asaah et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of the ratio of root number in the top 1.8 m of soil to trunk volume has shown that Casuarina equisetifolia and Markhamia lutea had significantly higher ratios than A. acuminata, Maesopsis eminii, and Grevillea robusta; Casuarina and Maesopsis were most competitive with crops, whereas Markhamia and Grevillea were least competitive. Tree propagation method also affects root architecture, and hence, potentially, competition (Mulatya et al, 2002;Asaah et al, 2010Asaah et al, , 2012.…”
Section: Why Tree Root Distribution Mattersmentioning
confidence: 98%